Consensus Statement on Future Directions for the Behavioral and Social Sciences in Oral Health. (June 2022) - McNeil, D.W.; Randall, C.L.; Baker, S.; Borrelli, B.; Burgette, J.M.; Gibson, B.; Heaton, L.J.; Kitsaras, G.; McGrath, C.; Newton, J.T.
The behavioral and social sciences are central to understanding and addressing oral and craniofacial health, diseases, and conditions. With both basic and applied approaches, behavioral and social sciences are relevant to every discipline in dentistry and all dental, oral, and craniofacial sciences, as well as oral health promotion programs and health care delivery. Key to understanding multilevel, interacting influences on oral health behavior and outcomes, the behavioral and social sciences focus on individuals, families, groups, cultures, systems, societies, regions, and nations. Uniquely positioned to highlight the importance of racial, cultural, and other equity in oral health, the behavioral and social sciences necessitate a focus on both individuals and groups, societal reactions to them related to power, and environmental and other contextual factors. Presented here is a consensus statement that was produced through an iterative feedback process. The statement reflects the current state of knowledge in the behavioral and social oral health sciences and identifies future directions for the field, focusing on 4 key areas: behavioral and social theories and mechanisms related to oral health, use of multiple and novel methodologies in social and behavioral research and practice related to oral health, development and testing of behavioral and social interventions to promote oral health, and dissemination and implementation research for oral health. This statement was endorsed by over 400 individuals and groups from around the world and representing numerous disciplines in oral health and the behavioral and social sciences. Having reached consensus, action is needed to advance and further integrate and translate behavioral and social sciences into oral health research, oral health promotion and health care, and the training of those working to ensure oral health for all.